Meta-Analysis of Technology-Based Islamic Religious Education Learning: Analysis of Its Effectiveness and Heterogeneity - Sere, Idrus; Manaf, Abdul (Jurnal Pendidikan Progresif, 2023)
Meta-Analysis of Technology-Based Islamic Religious Education (PAI) Learning: Analysis of Its Effectiveness and Heterogeneity. Objective: This research aims to further examine the effectiveness of technology-based PAI learning on student learning achievement, as well as investigate what factors can influence its effectiveness. Method: The design used in this research was a meta-analysis of 18 primary studies that met the inclusion criteria. Results: The results of the analysis obtained a combined effect size of 1.498 (very large effect). It can be concluded that technology-based PAI learning has a very big influence on student learning achievement compared to conventional learning. Furthermore, heterogeneity analysis reveals that the variables of education level, sample size, and type of technology used can influence the effectiveness of technology-based islamic religious education learning on student learning achievement. Conclusion: This meta-analysis can provide more objective results regarding various effect size variations regarding the effectiveness of technology-based PAI learning. Keywords: pai, technology-based learning, meta-analysis. DOI: http://dx.doi.org/10.23960/jpp.v13.i3.202312